Live Attenuated aTJ Vaccine Effectively Protects Pigeons Against Homologous PPMV-1 Challenge - Shan Zhang; Dahu Liu; Baojing Liu; Ruinying Liang; Lin Liang; Xinming Tang; Shaohua Hou; Chan Ding; Xusheng Qiu; Jiabo Ding (Vaccines)
Background: Pigeon paramyxovirus type 1 (PPMV-1) is a significant pathogen affecting pigeon populations globally. The commonly used La Sota vaccine provides limited protection due to antigenic divergence from circulating PPMV-1 strains. An antigenically matched vaccine is needed to address this challenge. Methods: An attenuated aTJ strain was developed through reverse genetics by modifying the F protein cleavage site of the virulent TJ-WT strain. Pigeons were immunized twice with the aTJ strain via eyedrop and intranasal routes, followed by a challenge with a virulent PPMV-1 strain ten days after the booster immunization. Results: The attenuated aTJ strain induced robust serum antibody titers post-booster immunization, and vaccinated pigeons showed strong protection upon challenge, with significantly reduced morbidity, mortality, and viral shedding compared to controls. Conclusions: These findings suggest that the aTJ strain is a promising candidate for the promotion of PPMV-1 prevention and control, emphasizing the importance of antigenic matching in optimizing vaccine efficacy.